2019
DOI: 10.1587/transinf.2018edp7132
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized Level Set Method Based on QPSO and Fuzzy Clustering

Abstract: A new fuzzy level set method (FLSM) based on the global search capability of quantum particle swarm optimization (QPSO) is proposed to improve the stability and precision of image segmentation, and reduce the sensitivity of initialization. The new combination of QPSO-FLSM algorithm iteratively optimizes initial contours using the QPSO method and fuzzy c-means clustering, and then utilizes level set method (LSM) to segment images. The new algorithm exploits the global search capability of QPSO to obtain a stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…The simulation results revealed that compared with the artificial neural network (ANN) and classical meta-heuristic optimization algorithm, QPSO exhibited advantages in accuracy, robustness, and rapid convergence to the global optimum. Yang et al [20] used QPSO to solve image segmentation and found that, compared with other optimization algorithms, QPSO improved the stability and accuracy of image segmentation. The economic dispatch problem in power systems is a typical high-dimensional nonlinear problem.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…The simulation results revealed that compared with the artificial neural network (ANN) and classical meta-heuristic optimization algorithm, QPSO exhibited advantages in accuracy, robustness, and rapid convergence to the global optimum. Yang et al [20] used QPSO to solve image segmentation and found that, compared with other optimization algorithms, QPSO improved the stability and accuracy of image segmentation. The economic dispatch problem in power systems is a typical high-dimensional nonlinear problem.…”
Section: Related Workmentioning
confidence: 99%
“…The equivalent division of the qualitative indicators includes qualitative language descriptions and corresponding quantitative data intervals. 5) [5, 10) [10, 100] R 12 (%) [0, 5) [5, 10) [10, 20) [20, 40) [40, 100] R 13 [0, 3) [3, 5) [5, 10) [10, 20) [20, 100] R 14 (%) [0, 5) [5, 10) [10, 20) [20, 40) [40, 100] R 15 (%) [0, 5) [5, 10) [10, 20) [20, 40) [40, 100] R 21 (%) [0, 1) [1, 3) [3, 5) [5, 10) [10, 100] R 22 (%) [0, 1) [1, 3) [3, 5) [5, 10) [10, 100] R 23 (%) [0, 3) [3, 5) [5, 10) [10, 20) [20, 100] R 24 (%) [0, 3) [3, 5) [5, 10) [10, [90, 95) [85, 90) [80, 85) [0, 80) R 34 (%) [0, 3) [3, 5) [5, 10) [10, 20) [20, 100] R 41 (mm) [0, 30) [30, 50) [50, PSO is a meta-heuristic method that can realize the global optimization of multiextremum functions. The particles in the population search for the global optimum of the function via cooperation and competition and share or exchange the information they obtained in their respective search processes.…”
Section: Classification Of Early Warning Levelsmentioning
confidence: 99%
See 3 more Smart Citations